Inguinodynia following inguinal hernia repair: a comparative analysis of open Lichtenstein and laparoscopic TAPP techniques in a two-center cohort - Aljaiuossi, Anas; Ba-shammakh, Saleh A.; Bani Hani, Mohammad; Al-A'athal, Musab; Abu-Hussein, Mohammad; Sobh, Mohammed; Yousef, Mohammad; Mesmar, Zaid; Dowais, Raad; Ababneh, Aseel W.; Kenani, Ahmad; Ababneh, Mohammad; et al. (Frontiers in Surgery, 2025)
BackgroundChronic postoperative groin pain (inguinodynia) is a major determinant of patient-reported outcomes after inguinal hernia repair. Evidence comparing open Lichtenstein hernioplasty (LICH) with laparoscopic trans-abdominal pre-peritoneal repair (TAPP) in everyday practice remains limited.MethodsWe performed a retrospective, two-centre cohort study of adults who underwent elective primary or recurrent inguinal hernia repair at King Abdullah University Hospital and Princess Basma Hospital (2010–2020). Patients were assigned to LICH (n = 107) or TAPP (n = 103). The primary endpoint was inguinodynia, defined as pain persisting ≥3 months post-operatively. Secondary endpoints included length of stay (LOS) and surgical complications. Multivariate logistic regression adjusted for age, body-mass index, smoking, hypertension, diabetes and benign prostatic hyperplasia.ResultsBaseline demographics were comparable, although hypertension (28% vs. 15.5%, p = 0.045) and current smoking (41.1% vs. 25.2%, p = 0.020) were more prevalent in the LICH group. Inguinodynia occurred in 23 LICH patients (21.5%) and 9 TAPP patients (8.7%) (p = 0.013). After risk adjustment, LICH remained an independent predictor of chronic pain (adjusted OR = 2.98; 95% CI 1.28–6.97; p = 0.012). Median LOS was slightly longer after LICH (2.40 ± 1.40 days) than TAPP (2.02 ± 0.89 days; p = 0.039). Overall rates of hematoma, seroma, surgical-site infection and early recurrence were low and did not differ significantly between techniques.ConclusionTAPP markedly lowers chronic pain and shortens hospital stay without extra morbidity, supporting its preferential use when expertise permits.